The influence of particle shape on screening: case studies regarding DEM simulations. Issue 3 (8th May 2018) - Wang, Xiaoyue; Li, Zhanfu; Tong, Xin; Ge, Xiaole
Abstract : Purpose: The purpose of this study is to explore how particle shape influences the screening, including screening efficiency per unit time, and the relationship between vibration parameters and screening efficiency per unit time in discrete element method (DEM) numerical simulations. Design/methodology/approach: In this paper, a three-dimensional discrete element model of vibrating screen with composite vibration form of swing and translation was proposed to simulate the screening process. In total, 11 kinds of non-spherical particles whose shapes changed in a continuous regularity gradual process were established using a multi-sphere method. In the DEM simulations, vibration parameters, including vibration frequency, vibration amplitude and stroke angle, and swing parameters, including swing frequency and swing angle, were changed to perform parametric studies. Findings: It shows that the effect of particle shape on screening efficiency is quantitative actually. However, the trends of different shape particles' screening efficiency per unit time are mainly consistent. Originality/value: Some simple particle shapes can be expected to be explored to do screening simulation studies reasonably with modification of the simulation data in DEM numerical simulations. That may improve the computational efficiency of numerical simulations and provide guidance to the study of the screening process.